Stability study and dynamical analysis of the multicellular chopper. (2018) - Djondiné, Philippe; Barbot, Jean-Pierre; Ghanes, Malek
The dynamical properties of a two-cells chopper connected to a particular nonlinear load are described in this paper. Some interesting and complex attractors are obtained. We analyse the system by means of Lyapunov exponents, fractal dimension, Poincaré mapping, first return, bifurcation diagram and phase portraits, respectively. Our model is described by a continuous time three-dimensional non-autonomous system and displays two-scroll chaotic attractors for certain values of its parameters. The numerical simulation is used to figure out their chaotic attractors. The analysis results show clearly that this is a new chaotic system which deserves further detailed investigation. Finally, phase portraits are obtained by using MATLAB/Simulink, which validates the theoretical analysis results.